Development of Causative Treatment Strategies for Lacrimal Gland Insufficiency by Tissue Engineering and Cell Therapy. Part 1: Regeneration of Lacrimal Gland Tissue: Can We Stimulate Lacrimal Gland Renewal In Vivo?. (1st September 2016) - Dietrich, Jana; Massie, Isobel; Roth, Mathias; Geerling, Gerd; Mertsch, Sonja; Schrader, Stefan
ABSTRACT: Severe dry eye syndrome (DES) is a complex disease that is commonly caused by inflammatory and degenerative changes in the lacrimal gland, and can result in severe pain and disruption to visual acuity. In healthy subjects, the ocular surface is continually lubricated by the tear film that ensures that the ocular surface remains moist and free of debris, enabling normal vision. The lacrimal fluid, mid-layer of the tear film, is mainly produced by the lacrimal gland and if this is dysfunctional for any reason, severe DES can develop. Currently, only palliative treatments for DES exist that aim to either replace or retain tears and/or minimize inflammation. A curative approach that aims to trigger the regeneration of existing lacrimal gland tissue in situ may, therefore, be very beneficial to DES patients. This article reviews the different approaches that have been explored toward lacrimal gland regeneration. Progress to date in vitro, in vivo, and in man is described with a focus on clinical feasibility and efficacy. Promising candidates for drug-dependent treatment of DES are growth factors and cytokines, such as hepatocyte growth factor (HGF) and tumor necrosis factor α-stimulated gene 6 protein (TSG-6). Only a few studies have evaluated gene therapy for lacrimal gland deficiencies, but with promising results. However gene therapy carries a variety of risks regarding carcinogenesis and therefore a treatment in the near future using this approach seems to be unlikely. Cell therapies utilizing mesenchymal stem cells (MSCs) seem to be more applicable than those using human amniotic membrane (hAM) epithelial cells or induced pluripotent stem (iPS) cells, since MSCs combine the favorable traits of both (multipotency, capability to stimulate regeneration immunomodulatory and non-immunogenic properties).